2008
DOI: 10.1080/00365540701587002
|View full text |Cite
|
Sign up to set email alerts
|

Home sampling and pooling of vaginal samples are effective tools for genetic screening of Chlamydia trachomatis among high school female students in Lithuania

Abstract: The aims were 1) to estimate the prevalence of C. trachomatis infection among sexually active female students in Kaunas, Lithuania; 2) to investigate the usefulness of personal invitation, self-sampling, and pooling of samples for screening; and 3) to evaluate the costs of the approaches used. A cross-sectional study inviting 795 female students (18-31 y of age) from 7 high schools and 1 college in Kaunas was performed. The response rate was 67% (533/795). Self-obtained vaginal samples were analysed, individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…A prevalence of 6.9% among women and 2.7% among men (18–35 years of age; 11% among women 18–20 years of age) in a population-based sample was reported in Estonia 50. A study conducted among female college students in Lithuania reported a 5.6% prevalence among participants aged 18–31 years (7.1% among sexually active female students 20–24 years of age) 51. In contrast, a Slovenian study found 3% of men and 1.6% of women infected with chlamydia (4.1% among men and women aged 18–24 years) 52…”
Section: Resultsmentioning
confidence: 95%
“…A prevalence of 6.9% among women and 2.7% among men (18–35 years of age; 11% among women 18–20 years of age) in a population-based sample was reported in Estonia 50. A study conducted among female college students in Lithuania reported a 5.6% prevalence among participants aged 18–31 years (7.1% among sexually active female students 20–24 years of age) 51. In contrast, a Slovenian study found 3% of men and 1.6% of women infected with chlamydia (4.1% among men and women aged 18–24 years) 52…”
Section: Resultsmentioning
confidence: 95%
“…The current variation in the risk for sexually transmitted infection may therefore partly be a function of the individuals' earlier sexual history instead of sociodemographic differences. PA may, for example, explain the lack of sociodemographic predictors (except age) for genital chlamydia (34). Thus, strategic intervention programs that focus on traditional risk groups may be less effective because a substantial group of individuals with a high number of partners might not be targeted.…”
Section: Discussionmentioning
confidence: 99%
“…Personal invitation of young female high-school students by providing information during lectures combined with kits for home sampling by vaginal swabs resulted in a response rate of 67% in Lithuania [17]. In a large US study [18 ] in which groups of high-school students attended an educational and screening session, more than 65% of the students attended for a urine-based C. trachomatis test.…”
Section: Prior Studiesmentioning
confidence: 98%